Lending credibility : the International Monetary Fund and the post-communist transition - Stone, Randall W., 1966- (Princeton, N.J. : Princeton University Press, 2002)
'With the end of the Cold War, the International Monetary Fund emerged as the most powerful international institution in history. But how much influence can the IMF exert over fiercely contested issues in domestic politics that affect the lives of millions? In Lending Credibility, Randall Stone develops the first systematic approach to answering this question. Deploying an arsenal of methods from a range of social sciences rarely combined, he mounts a forceful challenge to conventional wisdom. Focusing on the former Soviet bloc, Stone finds that the IMF is neither as powerful as some critics fear, nor as weak as others believe, but that the answer hinges on the complex factor of how much credibility it can muster from country to country. Stone begins by building a formal, game-theoretic model of lending credibility, which he then subjects to sophisticated quantitative testing on original data from twenty-six countries over the 1990s. Next come detailed, interview-based case studies on negotiations between the IMF and Russia, Ukraine, Poland, and Bulgaria. Stone asserts that the IMF has exerted startling influence over economic policy in smaller countries, such as Poland and Bulgaria. However, where U.S. foreign policy interests come more heavily into play, as in Russia, the IMF cannot credibly commit to enforcing the loans-for-policy contract. This erodes its ability to facilitate enduring market reforms. Stone's context is the postcommunist transition in Europe and Asia, but his findings carry implications for IMF activities the world over.' from publisher's description.
Cover; Title; Copyright; Contents; List of Figures; List of Tables; List of Acronyms; Preface; 1 Introduction; 1.1 The Strategy of Transition: Inflation and Democracy; 1.2 What Would We Like the IMF to Do?; I. Models and Data; 2 A Formal Model of Lending Credibility; 2.1 The Model; 2.2 The Equilibrium; 2.3 Hypotheses Derived from the Formal Model; 2.4 Conclusions; Appendix: A Formal Model of Lending Credibility; 3 Studying IMF Effectiveness; 3.1 Previous Research; 3.2 Critiques Raised in the Literature; 3.3 New Critiques; 3.4 Research Design; 3.5 Conclusions; 4 An Empirical Test of the Model.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: International Monetary Fund; Fonds monétaire international; International Monetary Fund; Fonds monétaire international; Europe, Eastern -- Economic policy -- 1989-; Europe, Eastern -- Economic conditions -- 1989-; Post-communism -- Europe, Eastern; Postcommunisme -- Europe de l'Est.; Europe de l'Est -- Politique économique -- 1989-; Europe de l'Est -- Conditions économiques -- 1989-; BUSINESS & ECONOMICS -- Banks & Banking; POLITICAL SCIENCE -- International Relations -- General; Economic history; Economic policy; Post-communism; Eastern Europe; Kredietverlening; Overheidsbeleid; Voormalige communistische landen; Economische hervormingen; Postcommunisme -- Europe de l'Est.; Europe de l'Est -- Conditions économiques -- 1989- ...; Europe de l'Est -- Politique économique -- 1989- ...; Since 1989; Electronic book